Patient–Physician Communication and Perception of Treatment Goals in Rheumatoid Arthritis: An Online Survey of Patients and Physicians - Shigeki Momohara; Kei Ikeda; Masahiro Tada; Toshiaki Miyamoto; Takanori Mito; Keita Fujimoto; Ayako Shoji; Eriko Wakita; Mitsumasa Kishimoto (Rheumatology and Therapy, 2023)
Abstract Introduction To evaluate patient–physician communication and patients’ understanding of treatment goals in rheumatoid arthritis (RA). Methods A cross-sectional online survey of patients with RA and physicians treating RA was conducted between 16 and 30 June 2021. Participants were asked to rate the importance of 17 goals on a 6-point Likert scale, and mean scores were compared between patients and physicians by the Wilcoxon rank sum test. Patients’ satisfaction with physician communication and their understanding of treatment goals were also assessed. Results The responses of 502 patients and 216 physicians were analyzed. The most common patient age group was 50–59 years (28.5%), and the mean disease duration was 10.3 years. Physicians had a mean of 19.2 years of treatment experience and were treating a mean of 44.3 patients. Among the 17 goals assessed, patients placed significantly more importance on drug tapering or discontinuation as short-term goals (3–6 months) and on performing basic activities of daily living, being able to engage in daily tasks, achieving and maintaining remission, maintaining better laboratory values, and drug tapering or discontinuation as long-term goals (5–10 years; all adjusted p < 0.05). Patient treatment satisfaction was significantly associated with disease activity, a feeling of treatment effectiveness, satisfaction with physician communication, and agreement with physician goals. Conclusion Differences exist among patients with RA and physicians treating RA regarding the importance of short- and long-term treatment goals. Good patient–physician communication appears to be important for improving patient satisfaction. Trial registration University Hospital Medical Information Network identifier: UMIN000044463.